The Influence of Information Technology and Human Resource Capability on Tenant Performance through Competitiveness at Soekarno-Hatta International Airport - Anhar Aktari Simatupang; Edi Abdurachman; Salahuddin Rafi (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
This study examines the effect of information technology and human resource capability on tenant performance at Soekarno-Hatta International Airport, with competitiveness as a mediating variable. The purpose of this study is to understand how the use of information technology and human resource capability can improve competitiveness and tenant performance in the competitive airport environment. The sample consisted of 150 tenant store managers, selected by stratified random sampling from a population of 675 tenants. A quantitative approach using structural equation modeling with partial least squares (SEM-PLS) was applied, with data collected through a five-point likert scale questionnaire. The results show that both information technology and human resource capability have significant effects on competitiveness. Information technology also has a direct effect on tenant performance, while human resource capability does not show a direct effect. Competitiveness plays a significant mediating role in strengthening the indirect relationship between information technology and  human resource capability with tenant performance.